2020
DOI: 10.1108/jcm-02-2019-3087
|View full text |Cite
|
Sign up to set email alerts
|

Music subculture as a source of conspicuous consumption practices: a qualitative content analysis of “altered movement” songs and music videos

Abstract: Purpose The purpose of this study is to focus on analyzing the role of music subcultures in the communication and promotion of conspicuous consumption practices. The object of study is the “altered movement” as the music style of the drug subculture in Mexico. Design/methodology/approach A qualitative content analysis of 78 lyrics and music videos of “altered movement” was carried out between August and December 2018. Findings The analysis of lyrics and music videos leads to the identification of four narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…However, the brand has been adopted as the drink of Mexican drug-traffickers. This brand appropriation is quite visible given the impact the narco cartels have on Mexican society and the large audiences reached by narco culture through narco corridos music and other cultural products and practices (Castillo Villar et al, 2020). The case study discusses how the nature of the group that has adopted the brand creates a dilemma for Diageo, which can neither openly oppose nor embrace this subculture's appropriation of one of its brands, thus opting to ignore it.…”
Section: Fall 2019: Traditional Case Study Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the brand has been adopted as the drink of Mexican drug-traffickers. This brand appropriation is quite visible given the impact the narco cartels have on Mexican society and the large audiences reached by narco culture through narco corridos music and other cultural products and practices (Castillo Villar et al, 2020). The case study discusses how the nature of the group that has adopted the brand creates a dilemma for Diageo, which can neither openly oppose nor embrace this subculture's appropriation of one of its brands, thus opting to ignore it.…”
Section: Fall 2019: Traditional Case Study Formatmentioning
confidence: 99%
“…As this was a Marketing Communication course, we added a whole section presenting a summary of another paper that is also part of our ongoing project investigating the marketing implications of Narcoculture. For this paper (Castillo Villar et al, 2020) entitled "Music subculture as a source of conspicuous consumption practices: A qualitative content analysis of 'altered movement' songs and music videos." we analyzed the lyrics and video of 78 recent narcocorridos.…”
Section: Advantages Of the Online Format For A Business Case Studymentioning
confidence: 99%
“…Pop culture originates in the media, gains strength and consolidates within and beyond communication streams (Becko & Amaral, 2020), and has an expressive cultural dimension, as it implies an order of meanings and social positions, indicating information about whom it consumes, place it belongs to, status, social position, and identity-as well as happens in music consumption in general (Hesmondgalgh, 2013;Lonsdale, 2020, DeNora, 2017Greenberg & Rentfrow, 2017). Along these lines, some studies show how music videos and music genres can rectify negative values and attitudes, especially regarding female objectification and sexualization (Ey, 2014;Ey, 2016;Castillo-Villar, Cavazos-Arroyo, & Kervyn, 2020). Continued exposure to sexual and sexist images in the media can lead young people to overvalue physical appearance and lose their sense of identity (Stephens & Few, 2007;Ey, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that more studies be conducted to check this aspect in music videos. In the work of Castillo-Villar et al (2020), it was found how much the subculture of the "altered movement" in Mexico can propagate a discourse of sexualization and domination over the female gender, as well as to conduct harmful identity work, such as idolizing drug dealers and their lifestyle, as well as other elements of the drug world. The authors propose that further work be done on other musical genres, such as funk carioca, to verify the issue of musical narratives and lyrics leading to consumption as a signpost of identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation